A Simple Response Evaluation Method for Base-Isolation Building-Connection Hybrid Structural System under Long-Period and Long-Duration Ground Motion - Hayashi, Kohei; Fujita, Kohei; Tsuji, Masaaki; Takewaki, Izuru (Frontiers in Built Environment, 2018)
An innovative hybrid control building system of base-isolation and building-connection has been proposed in the previous study. This system has two advantages, (i) to resist an impulsive earthquake input through the base-isolation system and (ii) to withstand a long-duration earthquake input through the building-connection system. A simple response evaluation method without the need of nonlinear time-history response analysis is proposed here for this hybrid building system under a long-period and long-duration ground motion. An analytical expression is derived in the plastic deformation of an elastic-perfectly plastic single-degree-of-freedom (SDOF) model with viscous damping under the multi impulse which is the representative of long-period and long-duration ground motions. A transformation procedure of a base-isolation building-connection hybrid structural system into an SDOF model is proposed by introducing two steps, one is the reduction of the main base-isolated building to an SDOF system and the other is the reduction of the connecting oil dampers supported on a free wall to an oil damper with a newly introduced compensation factor on a rigid wall. Application of the analytical expression of the plastic deformation to the reduced SDOF model including the compensation factor on the connecting oil dampers enables the development of a simplified, but rather accurate response evaluation method. The time-history response analysis of the multi-degree-of-freedom (MDOF) model and the comparison with the proposed simplified formula make clear the accuracy and reliability of the proposed simplified response evaluation method.